This preview shows page 1. Sign up to view the full content.
Unformatted text preview: a, b with a > 0, L-1 [ F ( as + b )] = 1 a e-bt/a f ( t a ) 4). Find the inverse Laplace transform of ( s-2) e-s s 2-4 s + 3 5). Find the solution of the IVP y 00 + 3 y + 2 y = u 2 ( t ) , y (0) = 1 , y (0) = 0 6). Use the convolution integral to ﬁnd the Laplace transform of f ( t ) = Z t ( t-u ) e u du...
View Full Document
This note was uploaded on 10/19/2011 for the course MATH 3354 taught by Professor Drager during the Fall '08 term at Texas Tech.
- Fall '08
- Taylor Series